Pengaruh Kualitas Produk, Persepsi Harga dan Citra Merek Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Mie Gaga pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Jenderal Achmad Yani - Nufus, Neli Zakiyyatun; Ratnamurni, Elis Dwiana (J-MAS (Jurnal Manajemen dan Sains), 2024)
Consumption of instant noodles in Indonesia has increased, this is not comparable to the decline in the Mie Gaga index on the Top Brand Index of 0.5%. The aim of this research is to examine the influence of product quality, price perception and brand image on customer loyalty which is mediated by Mie Gaga customer satisfaction at the Faculty of Economics and Business, Jenderal Achmad Yani University. Validity, reliability, classical assumptions, multiple regression, and Sobel test instruments were all successful. This tool was used to collect data from male and female respondents from the Faculty of Economics and Business, Jenderal Achmad Yani University who had consumed Gaga noodles in various flavors. The number of respondents involved in this research was 125 people. Cross-sectional or one-shot study is the data collection method used. Four research hypotheses out of ten proposed are supported by empirical data. This research shows that customer satisfaction can be influenced by product quality on customer loyalty. However, future researchers can use other ideas to influence customer loyalty directly. The results of this research will also help decision makers in similar companies when they create relevant strategies or programs